القيم النضالية الشخصية الرئيسية في رواية في سبيل التاج لمصطفي لطفي المنفلوطي: تحليل سوسيولوجي الأدب - Vita Diana, Ermawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The problem in this research is the value of the struggle of the main character contained in the novel Fi Sabili at-Taj by Mushtafa Luthfi al-Manfaluthi. The purpose of this research is to find out, describe, and analyze the values ​​of the struggle of the main character in the novel Fi Sabili at Taj by Mushtafa Luthfi al Manfaluthi in solving the problems at hand. Based on the source of the data studied, the researcher found the value of the struggle shown by the main character. The results of this study are that there are eight values ​​of struggle, namely the value of self-sacrifice, the value of unity, the value of respect, the value of patience and the spirit of never giving up, the value of cooperation, the value of love for the country, the value of hard work and the value of national spirit. The novel Fi Sabili at-Taj contains a good story about the struggle to defend the nation and state so that it can build the character of defenders of the nation and state.